Engaging islamic feminism: Provincializing feminism as a master narrative - Barlas, Asma (Islamic feminism: Current perspectives, 2008)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discours dominant; fem3400; féminisme islamique; premier cycle; périodes historiques; ressource en ligne; systèmes d'oppressions

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions--racism and Islamophobia--in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques